2011
DOI: 10.1007/s00586-010-1685-2
|View full text |Cite
|
Sign up to set email alerts
|

Sotos syndrome and scoliosis surgical treatment: a 10-year follow-up

Abstract: Sotos syndrome is caused by a gene deletion with an autosomal dominant pattern of inheritance. Cerebral gigantism, hypotonia and joint hyperextensibility are characteristic features of this syndrome. A percentage of these patients develop progressive scoliosis early in life. In the literature, few studies on the evolution of scoliosis in Sotos syndrome have been published. We retrospectively evaluated eight patients diagnosed with Sotos syndrome and scoliosis treated at the Garrahan Children Hospital between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Scoliosis is recognized to be a common symptom associated with Sotos syndrome, with Sotos et al reporting a case with mild scoliosis in their original series of five patients 16 and confirming the association in a later report 12–16 . Although the causes or factors that predispose Sotos syndrome patients to scoliosis remain unknown, scoliosis has been observed in approximately one-third of patients with variable severity 1 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Scoliosis is recognized to be a common symptom associated with Sotos syndrome, with Sotos et al reporting a case with mild scoliosis in their original series of five patients 16 and confirming the association in a later report 12–16 . Although the causes or factors that predispose Sotos syndrome patients to scoliosis remain unknown, scoliosis has been observed in approximately one-third of patients with variable severity 1 .…”
Section: Discussionmentioning
confidence: 94%
“…1 Scoliosis is recognized to be a common symptom associated with Sotos syndrome, with Sotos et al reporting a case with mild scoliosis in their original series of five patients 16 and confirming the association in a later report. [12][13][14][15][16] Although the causes or factors that predispose Sotos syndrome patients to scoliosis remain unknown, scoliosis has been observed in approximately one-third of patients with variable severity. 1 Examination into the genetic background of the 25 scoliosis patients with NSD1 aberrations in this study revealed that the 20 patients with microdeletions had more prominent and progressive scoliosis compared to the five patients with mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation